Knowledge generation in reproductive health research centers: A step towards the youth of the Iranian population - Baradaran Eftekhari, Monir; Falahat, Katayoun; Shakeri, Hanieh (Archives of Men’s Health, 2024)
Background: Reproductive health is a focal point for governments during this epidemiological transition. By adopting innovative research strategies, reproductive health research centers can determine priorities and practical measures. They can also take impactful steps toward protecting family development and decreasing the population’s average age through knowledge production. Therefore, this study is designed to investigate the knowledge production in reproductive health research centers in Iran during 2017-2021. Methods: Reproductive health research centers active for 5 or more years were evaluated during 2017-2021. In this study, three main axes including stewardship, knowledge production, and impact were evaluated with 15 key indicators. Results: This evaluation included 28 research centers related to reproductive and family health with at least 5 years of activity across 17 universities of medical sciences or organizations affiliated with the Ministry of Health in Iran. The final scores were calculated by summing the scores across the different axes. Based on the overall score, the top three research centers include (1) the Reproductive Biomedicine Research Center at the Academic Center for Education, Culture, and Research (ACECR), (2) the Reproductive Biotechnology Research Center at the (ACECR) and (3) the Preventive Medicine and Public Health research center at Iran University of Medical Sciences. Conclusion: Mission-oriented research activities in reproductive health research centers with the priority of treating infertility and childbearing care are effective in reducing the problem of population aging.